Ultrasonographic measurement of uterine lower segment scar thickness in cases of previous one caesarean section and obstetric outcome - Ganapathi, Trupthi; Chaudhari, Hemangi K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Vaginal birth after caesarean section (VBAC) has become an integral part of modern obstetrics with more than 1lakh VBACs achieved each year nationwide. Several studies have reported perinatal risks associated with failed trial of labour and uterine rupture in women attempting VBAC, due to concerns about these complications, the rate of VBAC deliveries has continued to fall in developed countries, with an inverse increase in Caesarean Sections (CS). To better assess the risk of uterine rupture, many authors have proposed sonographic measurement of scar or lower uterine segment (LUS) thickness near term, assuming that there is an inverse correlation between LUS thickness and the risk of uterine scar defect. Therefore, this assessment for the management of women with prior CS has increased safety by selecting women with the lowest risk of uterine rupture. Methods: Present study was a prospective observational study which assessed the obstetric outcome in women with previous lower segment caesarean section willing for trial of labour. Secondly, authors aimed to ascertain the best cut off values for predicting uterine rupture. Results: Present study found that as duration between previous LSCS and next pregnancy increased there was better chance of VBAC. As the baby weight increased VBAC rate reduced. Study also showed that scar thickness of 2.55mm and above measured by transabdominal method in the third trimester can be safely given trial of VBAC. Conclusions: Authors thus conclude that measurement of lower uterine segment/ scar thickness can help obstetrician decide whether VBAC is safe or not in patients with previous one LSCS willing for VBAC. Scar thickness of more than 2.55mm can be given safe trial of labour in women with previous one lower segment caesarean section.